Venous ulcer: risk factors and the Nursing Outcomes Classification - de Almeida Medeiros, Ana Beatriz; Farias de Queiroz Frazão, Cecília Maria; Dantas de Sá Tinôco, Jéssica; Mariano Nunes de Paiva, Maria das Graças; Venícios de Oliveira Lopes, Marcos; Brandão de Carvalho Lira, Ana Luisa (Investigación y Educación en Enfermería, 2014)
Objective. To explore the relationship between the risk factors for the development of venous ulcers and the indicators of tissue integrity from the Nursing Outcomes Classification. Methodology. A cross-sectional study conducted in 2013 in a university hospital in Natal/RN (Brazil). Fifty individuals selected by consecutive sampling participated in an interview and physical examination. Results. The most important risk factors were: 44% presented with arterial hypertension, 26% allergy, 20% diabetes mellitus, 4% participated in some physical activity, 6% were smokers and 14% drank alcohol. There was a statistically significant association between diabetes mellitus and the texture of the lesion (p=0.015) and tissue perfusion (p=0.026); allergy and texture (p=0.034); physical activity and hydration (p = 0.034); smoking and thickness (p = 0.018); and alcoholism and exudate of the ulcer (p=0.045). Conclusion. The relationship between risk factors and the nursing outcome indicators generated information relevant to the development of guidelines for the monitoring and treatment of venous ulcer information.